Nursing Care Practice in Neonatal Care Units of Tertiary Hospitals of Nepal: An Exploratory Qualitative Study - Shrestha, Tumla; Bista, Archana Pandey; Subedi, Madhusudan (Journal of Health Promotion, 2023)
Preterm infants (PTIs) require special care in neonatal care units (NCUs) for their survival, growth, and development. Nurses are in a pivotal position to provide quality care to those infants in NCUs. Available literature indicates that care practice needs to be improved in developing countries. This study aimed to explore the nursing care practice for PTIs in NCUs. An exploratory qualitative study was conducted in NCUs of three public tertiary care hospitals in Kathmandu, Nepal, from November 2019 to February 2020. Data were collected through six focus group discussions among 40 nurses working in NCUs. The thematic analysis of qualitative data revealed standardized and inadequate care practices for PTIs in NCUs. Standard practices regarding thermal care, oxygen administration, nutritional care, and infection prevention were found. Inadequate care was identified regarding sleep protection, proper positioning, supportive sensory environment, and pain management. The study reported the standard care practice areas and areas for improvement to enhance nursing care in NCUs, such as pain management, sleep promotion, breastfeeding support, kangaroo mother care, and a supportive sensory environment. The findings have important implications for enhancing care practices for PTIs in NCUs, which is important for promoting the short- and long-term outcomes among PTIs.